Relationship between the voltage applied to MZM arms and the generation of optical frequency comb - I. Hammadi, Yousif; S. Mansour, Tahreer (International Journal of Engineering and Technology, 2018)
In this study, an optical frequency comb source (OFCS) based on a dual-drive Machâ€“Zehnder modulator (MZM) is constructed and theoretically demonstrated. A mathematical model of the constructed OFCS is then built to investigate the effect of the peak-to-peak radio frequency (RF) signals applied to the MZM arms on the generated optical frequency comb (OFC) lines at the MZM output. A dual-drive MZM, a continuous wave laser source, and an RF signal source are included in the OFCS. The chirp parameter can be controlled and 64 comb lines generated at a comb spacing of 25Â GHz by regulating voltages applied to the MZM arms. The developed OFCS is relatively simple but valuable. The generated OFC lines can be used for high data-rate transmission.Â Â